Teaching professional and technical communication: a practicum in a book - Bridgeford, Tracy, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
Guides instructors in topics covered in professional and technical communication (PCT) or introductory major courses. Theoretical and applied discussions about teaching of this diverse subject, including relevant pedagogical approaches, how to apply practical aspects of PTC theory, and how to design assignments.--Provided by publisher.
Introduction to teaching professional and technical communication: a practicum in a book / Tracy Bridgeford -- Rhetorical analysis: a foundational skill for PTC teachers / James Dubinsky -- Teaching students about style in technical communication / Dan Jones -- Teaching content strategy in professional and technical communication / Dave Clark -- Teaching genre in professional and technical communication / Brent Henze -- What do instructors need to know about teaching information graphics? A multiliteracies approach / Karla Saari Kitalong -- Designing teaching to teach design / Eva Brumberger -- Designing and writing procedures / David K. Farkas -- A primer for teaching ethics in professional and technical communication / Paul Dombrowski -- What do instructors need to know about teaching collaboration? / Peter England and Pam Brewer -- Teaching usability testing: coding usability testing data / Tharon W. Howard -- What do instructors need to know about teaching technical presentations? / Traci Nathans-Kelly and Christine G. Nicometo -- Teaching international and intercultural technical communication: a comparative online credibility approach / Kirk St. Amant.
Keywords: Communication of technical information -- Study and teaching; Technical writing -- Study and teaching